Host factor PLAC8 is required for pancreas infection by SARS-CoV-2 - Lesly Ibargüen-González; Sandra Heller; Darío López-García; Hanna Dietenberger; Thomas FE Barth; Patricia Gallego; Israel Fernández-Cadenas; Sayoa Alzate-Piñol; Catalina Crespí; Julieth A. Mena-Guerrero; Eugenia Cisneros-Barroso; Alejandro P. Ugalde; et al. (Communications Medicine)
Abstract Background Although COVID-19 initially caused great concern about respiratory symptoms, mounting evidence shows that also the pancreas is productively infected by SARS-CoV-2. However, the severity of pancreatic SARS-CoV-2 infection and its pathophysiology is still under debate. Here, we investigate the consequences of SARS-CoV-2 pancreatic infection and the role of the host factor Placenta-associated protein (PLAC8). Methods We analyze plasma levels of pancreatic enzymes and inflammatory markers in a retrospective cohort study of 120 COVID-19 patients distributed in 3 severity-stratified groups. We study the expression of SARS-CoV-2 and PLAC8 in the pancreas of deceased COVID-19 patients as well as in non-infected donors. We perform pseudovirus infection experiments in PLAC8 knock-out PDAC and human beta cell-derived cell lines and validate results with SARS-CoV-2 virus. Results We find that analysis of circulating pancreatic enzymes aid the stratification of patients according to COVID-19 severity and predicts outcomes. Interestingly, we find an association between PLAC8 expression and SARS-CoV-2 infection in postmortem analysis of COVID-19 patients both in the pancreas and in other bonafide SARS-CoV-2 target tissues. Functional experiments demonstrate the requirement of PLAC8 in SARS-CoV-2 pancreatic productive infection by pseudovirus and full SARS-CoV-2 infectious virus inoculum from Wuhan-1 and BA.1 strains. Finally, we observe an overlap between PLAC8 and SARS-CoV-2 immunoreactivities in the pancreas of deceased patients. Conclusions Our data indicate the human pancreas as a SARS-CoV-2 target with plausible signs of injury and demonstrate that the host factor PLAC8 is required for SARS-CoV-2 pancreatic infection, thus defining new target opportunities for COVID-19-associated pancreatic pathogenesis.